Misdiagnosed Uterine Rupture of an Advanced Cornual Pregnancy - Christian Linus Hastrup Sant; Poul Erik Andersen (Case Reports in Radiology)
Cornual pregnancy is a diagnostic and therapeutic challenge with potential severe consequences if uterine rupture occurs with following massive intraabdominal bleeding. We report a case of a misdiagnosed ruptured cornual pregnancy occurring at 21 weeks of gestation. Ultrasound examination and computer tomography revealed no sign of abnormal pregnancy. The correct diagnosis was first made at emergency laparotomy. Uterine rupture should be considered in pregnant women presenting with abdominal pain and haemodynamic instability.